Imaging blood-brain barrier dysfunction: A state-of-the-art review from a clinical perspective - Moyaert, Paulien; Padrela, Beatriz E.; Morgan, Catherine A.; Petr, Jan; Versijpt, Jan; Barkhof, Frederik; Jurkiewicz, Michael T.; Shao, Xingfeng; Oyeniran, Olujide; Manson, Tabitha; Wang, Danny J. J.; Günther, Matthias; et al. (Frontiers in Aging Neuroscience, 2023)
The blood-brain barrier (BBB) consists of specialized cells that tightly regulate the in- and outflow of molecules from the blood to brain parenchyma, protecting the brain’s microenvironment. If one of the BBB components starts to fail, its dysfunction can lead to a cascade of neuroinflammatory events leading to neuronal dysfunction and degeneration. Preliminary imaging findings suggest that BBB dysfunction could serve as an early diagnostic and prognostic biomarker for a number of neurological diseases. This review aims to provide clinicians with an overview of the emerging field of BBB imaging in humans by answering three key questions: (1. Disease) In which diseases could BBB imaging be useful? (2. Device) What are currently available imaging methods for evaluating BBB integrity? And (3. Distribution) what is the potential of BBB imaging in different environments, particularly in resource limited settings? We conclude that further advances are needed, such as the validation, standardization and implementation of readily available, low-cost and non-contrast BBB imaging techniques, for BBB imaging to be a useful clinical biomarker in both resource-limited and well-resourced settings.